Atopic and nonatopic eczema in adolescence: is there a difference?. (1st September 2015) - Johansson, E.K.; Ballardini, N.; Bergström, A.; Kull, I.; Wahlgren, C.‐F.
Summary: Background: There is limited information on clinical manifestations of atopic eczema (AE) and non‐AE in teenagers. Objectives: To describe the characteristics of adolescent eczema in the general population and to identify potential differences between AE and non‐AE in teenagers. Methods: Overall, 3108 teenagers were included from the population‐based BAMSE cohort and 2529 of these teenagers provided blood samples for analysis of specific IgE. At age 16 years, the teenagers answered questionnaires regarding the symptoms of eczema, asthma and rhinitis for the previous year. Results: The prevalence of eczema in adolescence was 9·6% ( n  =   297). More girls than boys had eczema (12·5% vs. 6·5%; P  <   0·001). The age at onset was usually within the first 2 years of life (48·8%), but onset in adolescence was also common (25·6%). Eczema was mild in 72·7% of cases, moderate in 16·8% and severe in 10·4%. Body folds were most frequently affected (73·4%). More than half of the teenagers with eczema had AE (59%). The teenagers with AE had more severe and more chronic eczema. Onset in infancy was most common in AE and onset in adolescence was most common in non‐AE. There were no major differences in location or seasonal variance between AE and non‐AE in adolescence. Conclusions: AE is more common than non‐AE among teenagers. More than one in four teenagers with eczema has moderate‐to‐severe disease. Onset in adolescence is common, especially for non‐AE. AE in adolescence has an earlier onset and is more chronic and more severe than non‐AE. Abstract : What's already known about this topic? The 1‐year prevalence of eczema in adolescence is around 10%. More girls than boys have eczema in adolescence. What does this study add? One in four teenagers with eczema at age 16 years have onset in adolescence and one in four adolescents with eczema have moderate‐to‐severe disease. Atopic eczema (AE) in adolescence has an earlier onset and is more chronic and more severe than non‐AE. Location and seasonality do not differ between AE and non‐AE in adolescence. Linked Comment: von Kobyletzki, Br J Dermatol 2015; 173: 889 .